2009
DOI: 10.1097/ana.0b013e318192d60e
|View full text |Cite
|
Sign up to set email alerts
|

EEG Entropy Values During Isoflurane, Sevoflurane and Halothane Anesthesia With and Without Nitrous Oxide

Abstract: We hypothesized that like bispectral index, entropy may be anesthetic agent specific. We carried out a study to assess the entropy values of different anesthetics at equi-minimal alveolar concentrations (MACs) with air and nitrous oxide as carrier gases. Thirty adult patients undergoing spine surgery were randomized to receive halothane, isoflurane, or sevoflurane, in 2 stages, (a) with air/oxygen mixture (2:1) and (b) in nitrous oxide/oxygen (2:1). Heart rate, mean arterial blood pressure, response entropy (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Mean RE and SE during 0.6 % Isoflurane and 66 % nitrous oxide maintenance anaesthesia were found to be 53.5 and 55.1 respectively in lumbar spine surgery patients [1]. Our patient would be expected to have slightly lower values while using 0.8 % Isoflurane.…”
Section: Discussionmentioning
confidence: 53%
“…Mean RE and SE during 0.6 % Isoflurane and 66 % nitrous oxide maintenance anaesthesia were found to be 53.5 and 55.1 respectively in lumbar spine surgery patients [1]. Our patient would be expected to have slightly lower values while using 0.8 % Isoflurane.…”
Section: Discussionmentioning
confidence: 53%
“…17 The patients in our study received midazolam as premedication and propofol as induction agent. In some studies, no premedication was allowed, 7,11,24 while in others, intravenous induction agents were avoided and anaesthesia was induced using a volatile anaesthetic and/or N 2 O. 2,5,10 Although GABA A agonists, such as midazolam, may decrease the analgesic effect of N 2 O, a small dose (7.5 mg) was administered two hours preoperatively in our study.…”
Section: Resultsmentioning
confidence: 93%
“…Surgical stimuli increase cortical electrical activity as measured by BIS, SEF95 and median power frequency. 27 Using the same entropy module as we did during surgical stimulation, Soto et al 24 and Prabhakar et al 7 found increased entropy after the addition of N 2 O during volatile agent administration. Prabhakar et al 7 observed an increase in entropy in the presence of N 2 O 66% and iso urane or sevo urane adjusted to an EMAC of 1.0 but a nonsigni cant decrease when end-tidal vapour concentrations were kept constant at 1.1% and 2% with the addition of N 2 O 66% (1.5 EMAC).…”
mentioning
confidence: 78%
See 2 more Smart Citations